The effectiveness of participatory ergonomics to prevent low-back and neck pain - results of a cluster randomized controlled trial - Maurice T Driessen; Karin I Proper; Johannes R Anema; Dirk L Knol; Paulien M Bongers; Allard J van der Beek (Nordic Association of Occupational Safety and Health (NOROSH), 2011)
OBJECTIVE: The aim of this randomized controlled trial (RCT) was to investigate the effectiveness of the Stay@Work participatory ergonomics (PE) program to prevent low-back and neck pain. METHODS: A total of 37 departments were randomly allocated to either the intervention (PE) or control group (no PE). During a six-hour meeting, working groups followed the PE steps and composed and prioritized ergonomic measures aimed at preventing low-back and neck pain. Subsequently, working groups were requested to implement the ergonomic measures in the departments. The primary outcomes were low-back and neck pain prevalence and secondary outcomes were pain intensity and duration. Data were collected by questionnaires at baseline, and after 3-, 6-, 9-, and 12-months follow-up. Additionally, the course of low-back and neck pain (transitions from no symptoms to symptoms and from symptoms to no symptoms) was modeled. RESULTS: The randomization procedure resulted in 19 intervention departments (N=1472 workers) and 18 control departments (N=1575 workers). After 12 months, the intervention was not more effective than the control group in reducing the prevalence of low-back and neck pain or reducing pain intensity and duration. PE did not increase the probability of preventing low-back pain [odds ratio (OR) 1.23, 95% confidence interval (95% CI) 0.97-1.57) or neck pain (OR 1.01, 95% CI 0.74-1.40). However, PE increased the probability of recovering from low-back pain (OR 1.41, 95% CI 1.01-1.96), but not from neck pain (OR 0.95, 95% CI 0.72-1.26). CONCLUSION: PE neither reduced low-back and neck pain prevalence nor pain intensity and duration nor was it effective in the prevention of low-back and neck pain or the recovery from neck pain. However, PE was more effective in the recovery from low-back pain.